Pengembangan Mobile Learning Berbasis Android Pada Mata Pelajaran Jaringan Dasar - Nurul Aini; Rasyid Hardi Wirasasmita; Muhammad Zamroni Uska (Universitas Hamzanwadi, 2018)
The purpose of this study is to find out (1) the development of Android-based m-learning on basic network subjects, (2) the feasibility of developed learning media, (3) Knowing students' responses to Android-based m-learning. The research method used is the Research and Development (R D) method. The type of research used is qualitative data and quantitative data. The development model used in the research is Sugiyono's research and development model. Data collection used is observation, interview, and questionnaire. Data analysis techniques use qualitative and quantitative data. The results showed that the Android-based learning media developed was very feasible to be used in the learning process. From media feasibility media experts obtain a percentage of feasibility of 95% with very feasible criteria. Meanwhile, the material feasibility experts obtained a percentage of feasibility of 88% with very feasible criteria. From the students' response the media's feasibility in product trials obtained a percentage of student response values by 80% with very high criteria. Thus this Android-based m-learning is suitable to be used as a learning media for students of class X majoring in computer engineering and networking on basic network material.